International Students in Multicultural Classrooms - Laela Hikmah Nurbatra (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2018)
Internationalization has been done in some Indonesian universities, including University of Muhammadiyah Malang. The program has opened a wider opportunity for foreign lecturers to share their experiences with the students within the University of Muhammadiyah Malang. In addition to that, this program has also provided a greater chance for international students to enroll at the university. The number of International students in the University of Muhamadiyah Malang indeed has increased over the years. In regards to that, this present study identified challenges faced by the international students in the multicultural classroom. In doing so, the study involved six international students from two different countries; China and Thailand. The students studied at English Language Education Department, Faculty of Teacher Training and Education. Using questionnaires and a semi-structured interview, this study analyzed the result thematically. The research findings revealed five areas of challenges that the International students experienced in the university.